Politik Akomodasionis Orde Baru Terhadap (Umat) Islam: Telaah Historis Kelahiran Perbankan Syariah - Noor Azmah Hidayati (Millah: Journal of Religious Studies, 2005)
This paper tries to study the history of Islamic banking in Indonesia, which has been developing fastly today. With assumption that there is an unseparated relation between economic development and political factor, the writer argues that the presence of Islamic banking in Indonesia couldn’t be separated with the change of New Order policy which firstly was antipathy toward Indonesian moslem then became more accommodated to them. The change of this policy ass for the writer caused besides by the need of supporting from Indonesian moslem to the New Order Regime for the balance of the less of military support, also for the awakening of santri's elite that add the bargaining position of their power vis-a-vis the government.